1999
DOI: 10.1021/ja984469u
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Cr+(6S,4D), Mn+(7S,5S), and Fe+(6D,4F): Reaction of Cr+, Mn+, and Fe+ with Water

Abstract: The study of the reaction of water with the first-row transition-metal ions is continued in this work. Here we report the study of the reaction of water with the middle (Cr+, Mn+, and Fe+) first-row transition-metal cations in both high- and low-spin states. In agreement with experimental observations, the oxides are predicted to be more reactive than the metal ions, and no exothermic products are observed. Formation of endothermic products is examined. An in-depth analysis of the reaction paths leading to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
109
3
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(126 citation statements)
references
References 42 publications
13
109
3
1
Order By: Relevance
“…Our results for relative state energies ∆E, equilibrium internuclear distance r e , and harmonic vibrational frequencies ω e are given in Tables 4-9, where they are also compared to previous theoretical 15,[87][88][89][90][91][92] and experimental [93][94][95] results. A point of special interest is the comparison to DFT+U 19,96 calculations, 15,92 in particular PBE+U, where +U denotes a Hubbard-like 96 correction, carried out with a plane wave (PW) basis.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Our results for relative state energies ∆E, equilibrium internuclear distance r e , and harmonic vibrational frequencies ω e are given in Tables 4-9, where they are also compared to previous theoretical 15,[87][88][89][90][91][92] and experimental [93][94][95] results. A point of special interest is the comparison to DFT+U 19,96 calculations, 15,92 in particular PBE+U, where +U denotes a Hubbard-like 96 correction, carried out with a plane wave (PW) basis.…”
Section: Resultsmentioning
confidence: 79%
“…69,86 Relativistic effects should be included for quantitative comparison with experiment, but one of our main goals here was to compare to previous theoretical calculations, which all neglected relativistic effects. 15,[87][88][89][90][91][92] It should also be noted that in NWChem, while analytical gradients are available for open-shell DFT, analytical Hessians are not. Therefore, the DFT harmonic vibrational frequencies ω e were calculated by numerical central differences.…”
Section: Methodsmentioning
confidence: 99%
“…22,23 TiO 2 , ZrO 2 , and HfO 2 oxides have also been utilized to catalyze the aromatization of C 6+ alkanes. 20 While chemical reactions of the bare transition metal oxide cations with H 2 have received a significant interest, [24][25][26][27][28][29][30][31][32][33][34][35][36][37] neutral metal oxides have gained much less attention. [38][39][40][41][42][43][44][45][46][47][48][49][50] Recently Zhou et al 51 have reported a combined experimental and theoretical study on the hydrogenation reactions by group V metal dioxides using matrix isolation spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Broad-band photolysis with a high-pressure mercury arc lamp yields the bare oxide VO [21]. The potential energy surfaces of water activation by first-row transition metal ions were calculated in a series of papers by Ugalde and coworkers [22][23][24][25][26], showing that the case of Fe + is a typical example of two-state-reactivity [27]. For V + , elimination of H 2 involves a curve crossing from the quintet to the triplet surface [24].…”
Section: Introductionmentioning
confidence: 99%